INFORMATION TECHNOLOGY GOVERNANCE IN THE CONTEXT OF HIGHER EDUCATION GOVERNANCE IN SOUTH AFRICA - Johl, C.; Von Solms, R.; Flowerday, S. (South African Journal of Higher Education, 2016)
Public higher education in South Africa is governed by the Higher Education Act (Act No. 101 of 1997). Governance of public higher education in South Africa is just one element of governance practised across the entire domain of government to ensure accountability to the citizens of the country. This paper refers to four different, but related, levels of governance that span the landscape of public higher education: firstly, within the global context, secondly, in the context of the country with all of its government ministries; thirdly, the “system” of education in the context of legislative governance within the public higher education sector in South Africa; and finally, the institutional governance arrangements required in terms of legislation or regulation, which will be reviewed with particular attention being given to IT governance. Further, the notion of “managerialism” will be discussed to provide some structure to the context in which governance is practised. IT governance, as a subset of institutional governance, within and across the public higher education system is subsequently addressed. Finally, the current absence of IT governance oversight or reporting to the public higher education authority and mechanisms to improve governance in the sector are discussed, which provide an indication of the value that can be created by the implementation of a best practice IT governance framework at institutional level. Accordingly, an IT governance framework can be used to measure the maturity of a wide range of IT processes that The layered approach to governance investigated in this paper provides insight into the factors that influence the ability to govern subsystems, particularly the IT subsystem, in the public higher education sector in South Africa.